Robot-Assisted Bimanual Training Improves Hand Function in Patients With Subacute Stroke: A Randomized Controlled Pilot Study - Ma, Di; Li, Xin; Xu, Quan; Yang, Fei; Feng, Yutong; Wang, Wenxu; Huang, Jian-Jia; Pei, Yu-Cheng; Pan, Yu (Frontiers in Neurology, 2022)
Study design: Pilot Randomized controlled study Background: Bimanual therapy is an effective neurorehabilitation therapy for the upper limb, but its application to the distal upper limb is limited due to methodological difficulties. Therefore, we applied an exoskeleton hand to perform robot-assisted task-oriented bimanual training (RBMT) in stroke patients. Objective: To characterize the effectiveness of RBMT in patients with hemiplegic stroke with upper-limb motor impairment. Interventions: A total of 19 sub-acute stroke patients (1-6 months from onset) were randomized and allocated to RBMT and conventional therapy (CT) groups. The RBMT and CT groups received 90 min training per day (RBMT: 60 min RBMT + 30 min CT; CT: 60 min CT for hand functional training + 30 min regular CT), 5 days per week, for 4 weeks (20 sessions during the experimental period). Assessments: Clinical assessments, including the Fugl‒Meyer assessment of the upper-extremity (FMA-UE), Action Research Arm Test (ARAT), and Wolf Motor Arm Function Test (WMFT), were conducted before and after the intervention. Results: Within-group analysis showed a significant improvement in the FMA-UE and WMFT in both the CT and RBMT groups. The significant improvement in the Fugl‒Meyer assessment of the wrist and hand for the distal part in the RBMT group occurred earlier than that in the CT group. A significant improvement in WMFT time was found in both groups, but the WMFT functional ability assessment was only found in the RBMT group. No significant improvements in ARAT assessment were observed in either the CT or RBMT groups. Compared with CT, significant improvements in terms of the proportion of minimally clinically important differences were found after RBMT in FMA-UE (chi-square = 4.34, p = 0.037). No adverse events were reported by any of the participants across all sessions. Conclusions: This study is the first to apply RBMT to the distal part of the upper limb. Both RBMT and CT are effective in improving the upper limb function of subacute stroke patients. The RBMT shows superior potential efficacy in facilitating the distal part of upper extremity motor function recovery in the early stage. Future randomized control studies with large sample ...